Concentration and purication of uranium solution using continuous ion exchange system - Thai, Le Quang; Tuan, Vu Khac; Quynh, Trinh Nguyen; Mo, Dao Thi; Ha, Nguyen Hong; Bay, Bui Thi (Vietnam Journal of Chemistry, 2012)
In uranium ore processing technology, treatment of leach liquors with a low uranium content by ion exchange is preferred. Uranium plants in the world applied many kinds of ion exchange systems, such as fixed bed column ion exchange (FBIX), resin in pulp (RIP), continuous ion exchange (CHEM-SEPS, NIMCIX, HIMSLEY, POSTER,...). Continuous ion exchange equipments that can overcome the difficulties encountered in traditional FBIX and the use of resin ion exchange for the concentration and purification of pregnant liquors have widely been used. A continuous ion exchange system similar to HIMSLEY was designed, made and a operational flowsheet wad developed to treat pregnant liquor obtained from leaching of sandstone ore. The system comprises an absorption column, an elution column and two resin transfer columns. Retent time of solution in elution column was calculated so that system can operate continuously on basis of mass balance. Operational flowsheet developed consists of distint periods: loading, elution, resin transfer and washing. Results of test showed that the system can operate well and simply. Using this system can reached uranium recovery effciency of 98%, eluate containing 11.5 g U/l.